THE IMPACT OF CORPORATE GOVERNANCE, PROFITABILITY AND LIQUIDITY ON DIVIDEND POLICY IN NON-CYCLICAL SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2021-2023 PERIOD - Bonal, Emilie Monique; Santioso, Linda (Graduate Program of Universitas Tarumanagara, 2025)
This study aims to empirically analyze the effect of board size, board independence, profitability, and liquidity on dividend policy in non-cyclical segment companies published on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The research utilized 90 valid data points obtained from 30 non-cyclical companies as the research sample. The sampling method employed purposive sampling technique. Hypothesis testing was conducted using multiple linear regression, with data processing carried out using E-Views version 12 software. The appropriate model for this multiple linear regression analysis is the Fixed Effect Model (FEM). This study uses Dividend Payout Ratio (DPR) as a parameter to measure the company's dividend policy. The finding of the data processing indicate that board size and board independence have a crucial good influence on dividend policy, while profitability and liquidity do not have a crucial effect on dividend policy.